Evaluating geological and geotechnical data for the study of land subsidence phenomena at the perimeter of the Amyntaio coalmine, Greece - P. Tzampoglou; C. Loupasakis (International Journal of Mining Science and Technology, 2018)
Land subsidence phenomena caused by the overexploitation of the aquifers require the holistic knowledge of the geological, tectonic, hydrogeological and especially the geotechnical conditions of the affected sites in order to be mitigated. The current paper focuses on the study of the phenomena taking place at the Amyntaio sub-basin, northern Greece, hosting the homonymous open pit coal mine, operating there the last two decades. The mining as well as the rising agriculture activities have led to a significant drawdown of the ground water level triggering extensive ground subsidence phenomena, causing damages at the nearby villages, infrastructure and farmlands. The production and evaluation of engineering geological–geotechnical maps as well as of thematic tectonic and hydrogeological maps proved that the knowledge of this data is crucial for the interpretation of the land subsidence mechanism and the spatial distribution of its effects. Keywords: Land subsidence, Geotechnical map, Overexploitation of the aquifer, Amyntaio basin